Окуневые верхнего Днестра - Опалатенко, Л.К. (Вестник зоологии, 1967)
Morpho-biological characteristic and economic value of the species of Percidae family was studied under the conditions of the upper Dniester. On the base of morphometric analysis of Perca fluviatilis, Aspro zingel, Acerina cernua, A. acerina of the upper Dniester, the author determines their differences from the typical forms in the structure of unpaired fins, in a number of scales in the lateral line and in a number of vertebrates. In the plastical characters no differences were found. The fish of the mentioned species is of good gustatory qualities and are the desirable components of the Dniester ichthyofauna. Pike perch very scanty at present time must be artifically bred in fishery farms.